High-strength and high-conductivity copper-based composite material and preparation method thereof
Through the two-stage dispersion preparation strategy and high-frequency mechanical vibration technology, the existing high-strength high-conducting copper-based composite materials have been solved, and the performance of the existing high-strength high-conducting copper-based composite materials has been reduced and the preparation cost is high in high temperature environments, achieving uniform dispersion and performance improvement of the materials, which is suitable for large-scale Industrialized production.
Patent Information
- Application Number
- CN202411509360.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
AI Technical Summary
The performance of existing high-strength, high-conducting copper-based composite materials has decreased in high temperature environments, high production cost and complex process, making it difficult to achieve large-scale industrial production.
Using the two-stage dispersion strategy, the two-stage dispersion of prefabricated copper-based and nanoceramic particles are added to improve the interface bonding strength, and the active elements are promoted to form a liquid-phase enrichment layer on the surface of nanoceramic particles through high-frequency mechanical vibration. , form solid solution coating to reduce interface energy and wettability and promote uniform distribution of nanoceramic particles.
The uniform dispersion of high-strength, high-conducting copper-based composite materials is achieved, which reduces the interface energy and wettability of the material, improves the mechanical and electrical conductivity of the material, and simplifies the preparation process and reduces production costs.
Smart Images

Figure CN119433253A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal-based composite materials and relates to a high-strength and high-conductivity copper-based composite material and a preparation method thereof. Background Art
[0002] As core conductor materials, copper-based composite materials are widely used in the electronic information industry (such as lead frames for ultra-large-scale integrated circuits), high-speed rail transit (such as overhead wires, high-power frequency-modulated and speed-regulated asynchronous traction motor bars and end rings), new energy vehicle industry (such as resistance welding electrodes, battery materials, charging pile elastic materials), metallurgical industry (such as continuous casting machine crystallizers, electric vacuum devices), etc., especially high-strength and high-conductivity copper alloys, which are widely used in various important components such as integrated circuit lead frame strips, rail transit contact wires, and high-voltage electrical contacts. Among them, chromium-zirconium copper, alumina dispersion-strengthened copper, and beryllium copper are representative materials, each of which has unique performance advantages and application scenarios, but also has some defects that are difficult to overcome.
[0003] As the first type of high-strength and high-conductivity copper-based materials, precipitation-strengthened alloys such as chromium-zirconium-copper improve the strength of the material through precipitation hardening. However, they are prone to softening and remelting in high-temperature environments, resulting in a significant decrease in material performance, thus limiting their application under high-temperature conditions. In addition, the microstructure of this type of alloy is complex and the requirements for the preparation process are relatively high.
[0004] The second type of alumina dispersion-strengthened copper-based materials disperses alumina particles evenly in the copper matrix by dispersion strengthening, thereby significantly improving the mechanical properties of the material. However, the preparation cost of this type of material is high, and the preparation method is complex and requires precise process control, so it is difficult to adapt to the needs of large-scale industrial production. At the same time, the interface reaction between alumina particles and the copper matrix is also one of the important factors affecting the material performance.
[0005] The third type of alloy materials, such as beryllium copper, improves the strength of the material by adding a large amount of alloy elements, but at the same time greatly reduces its electrical conductivity. This inverted relationship between electrical conductivity and mechanical properties limits the use of alloy materials such as beryllium copper in certain application scenarios that have strict requirements on electrical conductivity. In addition, the addition of alloy elements will also affect the processing performance and corrosion resistance of the material.
[0006] In the engineering world, the mainstream preparation method for high-strength and high-conductivity copper-based composite materials is powder metallurgy, which uses mechanical ball milling to mix metal powders and nano-ceramic particles. Although this method can produce dispersion-strengthened copper-based materials, it is expensive and complex, making it difficult to achieve large-scale industrial production. Therefore, it is urgent to find a more economical preparation method that can meet the needs of industrial applications while taking into account both electrical conductivity and mechanical properties. Summary of the invention
[0007] In view of this, the object of the present invention is to provide a high-strength and high-conductivity copper-based composite material and a preparation method thereof, which can reduce the preparation difficulty and production cost while taking into account both the conductive properties and the mechanical properties.
[0008] In a first aspect, the present invention provides a method for preparing a high-strength and high-conductivity copper-based composite material, comprising the following steps:
[0009] S1: taking out a part of the original copper base as a prefabricated copper base, melting the prefabricated copper base at high temperature into a prefabricated copper melt and keeping the temperature;
[0010] S2: adding active elements for improving the copper-based interface bonding strength to the prefabricated copper melt, and stirring and mixing to obtain a prefabricated copper alloy melt;
[0011] S3: adding nano-ceramic particles into the prefabricated copper alloy melt, and stirring and mixing, to obtain a copper alloy reinforced melt;
[0012] S4: melting the remaining original copper base at high temperature, adding the copper alloy reinforcement melt into the remaining base copper melt, and stirring and mixing, so as to obtain a copper alloy melt with nano-ceramic particles uniformly mixed;
[0013] S5: The copper alloy melt is cooled down accompanied by mechanical vibration. The mechanical vibration causes some active elements to precipitate from the copper matrix and form a uniform liquid enrichment layer on the surface of the nano-ceramic particles, and finally form a solid solution coating with the copper matrix on the surface of the nano-ceramic particles to reduce the interface energy and wettability of the copper matrix and nano-ceramic phases, thereby promoting the uniform distribution of nano-ceramic particles in the copper matrix to obtain a high-strength and high-conductivity copper-based composite material.
[0014] Optionally, in step S1, the mass of the prefabricated copper base is 1 / 5 to 1 / 30 of the mass of the original copper base, and the purity of the original copper base is 95 to 100 wt.%.
[0015] Optionally, the active element is one or a mixture of Co, Cr, Zr, Mg, Li, Be, Zn, Ni, Ag, Cd, Pd and rare earth elements Ce, La, Sc, Y.
[0016] Optionally, in step S2, the mass ratio of the active element to the copper in the original copper matrix is 0.001 wt.% to 10 wt.%.
[0017] Optionally, the nano-ceramic particles are one or more of WC, TiC, NbC, TaC, and Cr3C2.
[0018] Optionally, the purity of the nano-ceramic particles is 95-100wt.%, and the particle size is less than 150nm.
[0019] Optionally, in step S3, the volume fraction of the nano-ceramic particles in the copper alloy is 0.01 vol.% to 10 vol.%.
[0020] Optionally, the melting temperature of the copper-based prefabricated block and the original copper-based block is 1312°C to 1512°C.
[0021] Optionally, in steps S2, S3 and S4, the stirring and mixing is performed by one or a combination of mechanical stirring, ultrasonic stirring, mechanical vibration stirring, electromagnetic pulse stirring and electromagnetic stirring.
[0022] Optionally, the copper purity in the original copper matrix is not less than 99 wt.%.
[0023] Optionally, in step S5, the copper alloy melt is cooled down with high-frequency mechanical vibration, and the frequency of the high-frequency mechanical vibration is 500-1000 Hz.
[0024] In a second aspect, the present invention also provides a high-strength and high-conductivity copper-based composite material prepared according to the above method.
[0025] In a third aspect, the present invention further provides a copper alloy product, which is made of the above-mentioned high-strength and high-conductivity copper-based composite material.
[0026] The beneficial effects of the present invention are:
[0027] Firstly, the present invention adopts a two-stage dispersion preparation strategy, wherein the first stage dispersion is uniform dispersion of nano-ceramic particles in a prefabricated copper alloy melt, and the second stage dispersion is dispersion of the prefabricated copper alloy melt in a pure copper melt.
[0028] In the process of the first stage dispersion, the present invention pre-adds active elements and preliminarily disperses the nano-ceramic particles by stirring. The active elements and mechanical vibrations input energy into the copper alloy melt to a certain extent, thereby avoiding insufficient power for the migration of nano-particles due to insufficient energy input into the copper melt. This step lays a solid foundation for the subsequent dispersion process.
[0029] In the process of the second-stage dispersion, after the copper alloy reinforcement melt is smelted and diluted in the matrix copper melt, as the temperature decreases, some active elements are precipitated, and on the one hand, a liquid phase enrichment layer is formed on the surface of the nano-ceramic particles, thereby improving the interface bonding strength of the copper base to maintain the electrical conductivity of the copper base; on the other hand, the active elements can also reduce the wetting angle between the nano-ceramic particles and the copper base and form an active element liquid phase coating on the surface of the nano-ceramic particles, further promoting the uniform distribution of the nano-ceramic particles to improve the mechanical properties of the composite copper base. It can be seen that the preparation method provided by the present invention improves the dispersion efficiency of the nano-particles, ensures the uniformity of the dispersion, and takes into account the electrical conductivity and mechanical properties of the composite material.
[0030] Secondly, the present invention uses high-frequency mechanical vibration during the solidification process to promote the uniform coating of the active element liquid phase on the surface of the ceramic particles. At the same time, the solidification process accompanied by high-frequency vibration will obtain a refined equiaxed crystal structure copper ingot. This step is of great significance for improving the mechanical properties of the composite material. The refined equiaxed crystal structure can significantly improve the strength and toughness of the material, while reducing the thermal cracking tendency of the material, and improving the processing performance and service life of the material.
[0031] In addition, compared with the existing preparation methods, the preparation method of the present invention has significant advantages. Traditional preparation methods often have problems such as complicated operation steps and high production costs. However, the present invention simplifies the operation steps and reduces the production cost through the two-stage preparation and step-by-step dispersion strategy.
[0032] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0034] Figure 1 A flow chart of a method for preparing a high-strength and high-conductivity copper-based composite material provided by the present invention;
[0035] Figure 2 This is the SEM image of the copper-based composite material obtained by powder metallurgy;
[0036] Figure 3 This is a SEM image of the copper-based composite material obtained in Example 1 of the present invention;
[0037] Figure 4 This is a SEM image of the copper-based composite material obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0038] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and the features in the embodiments can be combined with each other without conflict.
[0039] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0040] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0041] The current copper-based materials have an inverse relationship between electrical conductivity and mechanical properties, which is one of the main reasons that restrict the narrow application range of copper-based materials. Dispersion-strengthened copper-based composite materials can greatly improve their mechanical properties while sacrificing little electrical conductivity. The current mainstream preparation method is to use powder metallurgy to prepare dispersion-strengthened copper-based materials, such as Figure 2 As shown in FIG. 1 , the uniformity of the nano-ceramic particles obtained is limited, and the nano-ceramic particles are more agglomerated. In addition, the cost is high and the process is complicated, making it difficult to achieve large-scale industrial production. Based on this, an embodiment of the present invention provides a method for preparing a high-strength and high-conductivity copper-based composite material, such as Figure 1 As shown, the following steps are included:
[0042] S1: taking out a part of the original copper base as a prefabricated copper base, melting the prefabricated copper base at high temperature into a prefabricated copper melt and keeping the temperature;
[0043] S2: adding active elements for improving the copper-based interface bonding strength to the prefabricated copper melt, and stirring and mixing to obtain a prefabricated copper alloy melt;
[0044] S3: adding nano-ceramic particles into the prefabricated copper alloy melt, and stirring and mixing, to obtain a copper alloy reinforced melt;
[0045] S4: melting the remaining original copper base at high temperature, adding the copper alloy reinforcement melt into the remaining base copper melt, and stirring and mixing, so as to obtain a copper alloy melt with nano-ceramic particles uniformly mixed;
[0046] S5: The copper alloy melt is cast onto a high-frequency vibration casting table, and then cooled. The mechanical vibration causes some active elements to precipitate from the copper matrix and form a uniform liquid enrichment layer on the surface of the nano-ceramic particles. Finally, a solid solution coating is formed on the surface of the nano-ceramic particles with the copper matrix to reduce the interface energy and wettability of the copper matrix and nano-ceramic phases, thereby promoting the uniform distribution of nano-ceramic particles in the copper matrix to obtain a high-strength and high-conductivity copper-based composite material.
[0047] Specifically, in the embodiment of the present invention, the mass of the prefabricated copper matrix is 1 / 5 to 1 / 30 of the mass of the original copper matrix, and the purity of the original copper matrix is 95 to 100 wt.%.
[0048] Specifically, the active element is one or a mixture of Co, Cr, Zr, Mg, Li, Be, Zn, Ni, Ag, Cd, Pd and rare earth elements Ce, La, Sc, and Y.
[0049] Specifically, in the embodiment of the present invention, the mass ratio of the active element to the copper in the original copper matrix is 0.001 wt.% to 10 wt.%.
[0050] Specifically, in an embodiment of the present invention, the nano-ceramic particles are one or more of WC, TiC, NbC, TaC, and Cr3C2.
[0051] Specifically, in the embodiment of the present invention, the purity of the nano-ceramic particles is 95-100 wt.%, and the particle size is less than 150 nm. Further, the particle size of the nano-ceramic particles is preferably 10 nm to 100 nm.
[0052] Specifically, in an embodiment of the present invention, the volume fraction of the nano ceramic particles in the copper alloy is 0.01 vol.% to 10 vol.%.
[0053] Specifically, in the embodiment of the present invention, the melting temperature of the copper-based prefabricated block and the original copper-based block is 1312°C to 1512°C.
[0054] Specifically, in the embodiments of the present invention, the stirring and mixing involved in the preparation process adopts one or a combination of mechanical stirring, ultrasonic stirring, mechanical vibration stirring, electromagnetic pulse stirring and electromagnetic stirring.
[0055] Specifically, in an embodiment of the present invention, the purity of copper in the original copper matrix is not less than 99 wt.%.
[0056] Specifically, in the embodiments of the present invention, the entire preparation process is carried out in an inert gas.
[0057] Specifically, in an embodiment of the present invention, the vibration frequency of the high-frequency vibration casting table is 500-1000 Hz.
[0058] An embodiment of the present invention also provides a high-strength and high-conductivity copper-based composite material prepared according to the above method.
[0059] An embodiment of the present invention further provides a copper alloy product, which is mainly made of the above-mentioned high-strength and high-conductivity copper-based composite material.
[0060] Example 1
[0061] A method for preparing a high-strength and high-conductivity copper-based composite material, wherein Co is selected as an active element and WC is selected as nano-ceramic particles, and specifically comprises the following steps:
[0062] (1) The mass of the original copper base is 3000 g and the purity is 99 wt.% or above. 600 g of the mass is taken as the prefabricated copper base, which is smelted at 1400° C. to form a prefabricated copper melt, and the temperature is continuously kept. The whole process is carried out under the protection of inert gas;
[0063] (2) adding 6 g of Co with a purity of not less than 99 wt.% to the prefabricated copper melt, and then continuously mechanically stirring at 500 rpm for 10 min to obtain a prefabricated copper-cobalt alloy melt;
[0064] (3) weighing 54 g of WC particles with an average particle size of 150 nm and a purity of not less than 99 wt.% and adding them to the prefabricated copper-cobalt alloy melt, and then continuously mechanically stirring at 400 rpm for 20 min to obtain a copper-cobalt alloy reinforced melt;
[0065] (4) melting the remaining original copper matrix at 1350° C., adding the copper-cobalt alloy reinforcement melt into the remaining matrix copper melt, continuously stirring mechanically at 400 rpm for 20 min, and fully stirring and mixing to obtain a copper-cobalt alloy melt;
[0066] (5) Before the copper-cobalt alloy melt solidifies, it is cast onto a GZT200 high-frequency vibration casting table, and is cooled at a vibration frequency of 750 Hz at a cooling rate of 5°C / min to 20°C / min using a heat-insulating material. After complete solidification, the ingot is quenched and cooled to room temperature to obtain a Cu-Co-WC composite material.
[0067] The scanning electron microscopy results of the Cu-Co-WC composite material prepared in this embodiment are as follows: Figure 3 As shown, it can be seen that the WC particles are evenly distributed on the Cu surface without obvious agglomeration.
[0068] Example 2
[0069] A method for preparing a high-strength and high-conductivity copper-based composite material, wherein Co is selected as an active element and WC is selected as nano-ceramic particles, and specifically comprises the following steps:
[0070] (1) The mass of the original copper base is 3000 g and the purity is 99 wt.% or above. 600 g of the mass is taken as the prefabricated copper base, which is smelted at 1400° C. to form a prefabricated copper melt, and the temperature is continuously kept. The whole process is carried out under the protection of inert gas;
[0071] (2) adding 6 g of Co with a purity of not less than 99 wt.% to the prefabricated copper melt, and then continuously mechanically stirring at 500 rpm for 10 min to obtain a prefabricated copper-cobalt alloy melt;
[0072] (3) weighing 10.2 g of WC particles with an average particle size of 150 nm and a purity of not less than 99 wt.% and adding them to a prefabricated copper-cobalt alloy melt, and then continuously mechanically stirring at 400 rpm for 20 min to obtain a copper-cobalt alloy reinforced melt;
[0073] (4) melting the remaining original copper matrix at 1350° C., adding the copper-cobalt alloy reinforcement melt into the remaining matrix copper melt, continuously stirring mechanically at 400 rpm for 20 min, and fully stirring and mixing to obtain a copper-cobalt alloy melt;
[0074] (5) Before the copper-cobalt alloy melt solidifies, it is cast onto a GZT200 high-frequency vibration casting table, and is cooled at a vibration frequency of 750 Hz at a cooling rate of 5°C / min to 20°C / min using a heat-insulating material. After complete solidification, the ingot is quenched and cooled to room temperature to obtain a Cu-Co-WC composite material.
[0075] The scanning electron microscopy results of the Cu-Co-WC composite material prepared in this embodiment are as follows: Figure 3 As shown, it can be seen that the WC particles are evenly distributed on the Cu surface without obvious agglomeration.
[0076] Pure copper was used as a comparative sample, and the composite material prepared in Example 1 and the composite material prepared in Example 2 were used as experimental samples. The electrical conductivity, hardness and tensile strength thereof were tested respectively. The results are shown in Table 1.
[0077] Table 1
[0078]
[0079]
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a high-strength and high-conductivity copper-based composite material, characterized in that: The following steps are involved: S1: taking out a portion of the original copper base as a prefabricated copper base, smelting the prefabricated copper base at high temperature into a prefabricated copper melt and keeping the temperature; S2: adding active elements for improving the copper-based interface bonding strength to the prefabricated copper melt, and stirring and mixing to obtain a prefabricated copper alloy melt; S3: adding nano-ceramic particles into the prefabricated copper alloy melt, and stirring and mixing to obtain a copper alloy reinforced melt; S4: melting the remaining original copper base at high temperature, adding the copper alloy reinforcement melt into the remaining base copper melt, and stirring and mixing, so as to obtain a copper alloy melt with nano-ceramic particles uniformly mixed; S5: The copper alloy melt is cooled down accompanied by mechanical vibration. The mechanical vibration causes part of the active elements to precipitate from the copper matrix and form a uniform liquid enrichment layer on the surface of the nano-ceramic particles. Finally, a solid solution coating is formed with the copper matrix on the surface of the nano-ceramic particles to reduce the interface energy and wettability between the copper matrix and the nano-ceramic phases, thereby promoting the uniform distribution of the nano-ceramic particles in the copper matrix to obtain a high-strength and high-conductivity copper-based composite material.
2. The preparation method according to claim 1, characterized in that: In step S, the mass of the prefabricated copper base is 1 / 5 to 1 / 30 of the mass of the original copper base, and the purity of the original copper base is 95 to 100 wt.%.
3. The preparation method according to claim 1, characterized in that: The active element is one or a mixture of Co, Cr, Zr, Mg, Li, Be, Zn, Ni, Ag, Cd, Pd and rare earth elements Ce, La, Sc, Y.
4. The preparation method according to claim 3, characterized in that: In step S2, the mass ratio of the active element to the copper in the original copper matrix is 0.001 wt.% to 10 wt.%.
5. The preparation method according to claim 1, characterized in that: The nano ceramic particles are one or more of WC, TiC, NbC, TaC, and Cr3C2.
6. The preparation method according to claim 5, characterized in that: The purity of the nano ceramic particles is 95-100 wt.%, and the particle size is less than 150 nm.
7. The preparation method according to claim 5, characterized in that: In step S3, the volume fraction of the nano-ceramic particles in the copper alloy is 0.01 vol.% to 10 vol.%.
8. The preparation method according to claim 1, characterized in that: The melting temperature of the copper-based prefabricated block and the original copper-based block is 1312°C to 1512°C.
9. The preparation method according to claim 1, characterized in that: In steps S2, S3 and S4, the stirring and mixing is performed by one or a combination of mechanical stirring, ultrasonic stirring, mechanical vibration stirring, electromagnetic pulse stirring and electromagnetic stirring.
10. The preparation method according to claim 1, characterized in that: The purity of copper in the original copper matrix is not less than 99 wt.%.
11. The preparation method according to claim 1, characterized in that: In step S5, the copper alloy melt is cooled down with high-frequency mechanical vibration, and the frequency of the high-frequency mechanical vibration is 500-1000 Hz.
12. A high-strength and high-conductivity copper-based composite material prepared according to the method of any one of claims 1 to 11.
13. A copper alloy product, characterized in that: The copper alloy product is mainly made of the high-strength and high-conductivity copper-based composite material described in claim 12.